Additively manufacturable micro-mechanical logic gates - Yuanping Song (Nature Portfolio, 2019)
Mechanical computing based on the logic devices that utilize mechanical energy can be an alternative to conventional electronic computing. Here, Song et al. show a micromechanical logic gate, fabricated using multi-stable buckling flexures, which is capable of realizing all digital logic operations.